2014
DOI: 10.1111/1751-2980.12126
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor binding protein‐related protein 1 contributes to hepatic fibrogenesis

Abstract: IGFBP-rP1 contributes to the development of liver fibrosis and may be a novel molecule involved in the progression of hepatic fibrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
2
27
0
1
Order By: Relevance
“…IGFBP7 has been localized to the Weibel-Palade bodies (storage organelles) of endothelial cells (21). Furthermore, IGFBP7 has also been associated with collagen deposition (22) and may therefore also be linked with myocardial fibrosis. The syndrome of HFpEF has been recently proposed to be a pro-inflammatory state with production of reactive oxygen species by endothelial cells that subsequently results in concentric LV remodeling, stiffening of cardiomyocytes, and increased collagen deposition which all ultimately lead to diastolic dysfunction (23).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP7 has been localized to the Weibel-Palade bodies (storage organelles) of endothelial cells (21). Furthermore, IGFBP7 has also been associated with collagen deposition (22) and may therefore also be linked with myocardial fibrosis. The syndrome of HFpEF has been recently proposed to be a pro-inflammatory state with production of reactive oxygen species by endothelial cells that subsequently results in concentric LV remodeling, stiffening of cardiomyocytes, and increased collagen deposition which all ultimately lead to diastolic dysfunction (23).…”
Section: Discussionmentioning
confidence: 99%
“…Up to the present time numerous research efforts in the field of organ fibrosis have identified several polypeptide mediators important to the fibrotic process, such as platelet-derived growth factor, insulin-like growth factor binding protein-related protein 1, connective tissue growth factor, and transforming growth factor (TGF)-b1 (Bonner, 2004;Sureshbabu et al, 2011;Yu et al, 2013;Guo et al, 2014;Hao et al, 2014;Ma et al, 2014). Nevertheless, effective alternative targets and therapies are still urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP-7 has also been shown to attenuate liver fibrosis through the regulation of MMPs/TIMPs in mice [62]. IGFBPrP1 contributed to the development of liver fibrosis in fibrotic and cirrhotic tissue biopsy samples and may be a novel molecule involved in the progression of liver fibrogenesis [28]. Studies conducted in vitro found that IGFBPrP1 induced liver fibrosis by means of HSC activation and hepatocyte apoptosis through the Smad 2/3 signaling pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, serum IGFBP-3 concentrations are low, correlating with the severity of liver dysfunction, and signifying poor prognosis in hepatocellular carcinoma (HCC) [26]. In in vitro studies, IGFBP-7 expression has been found to hepatocyte apoptosis and HSC activation [27,28]. In relation to the participation of IGFBP-2, -5 and -6, there is little evidence of their concentrations in serum and the possible association with liver diseases.…”
Section: Igfbps and Liver Fibrosismentioning
confidence: 99%